Studi Peristiwa Dampak Revisi Renewable Energy Directive Terhadap Perusahaan Perkebunan Kelapa Sawit di Indonesia - Ilham Gresnaidi; Rahmat Agus Santoso; Anita Handayani (Jurnal Mahasiswa Manajemen, 2021)
Background - Indonesia is one of the most significant crude palm oil exported. But, the amendment of Renewable Energy Directive also brings impact to these industries. The content of the amendment that proposed is to minimize the use of crude palm oil in Europe, while Europe is also the biggest imported of Indonesia crude palm oil. Objective - This study aims to determine wether there is the difference on abnormal return before and after the proposed Delegated Act, European Parliament vote of proposed Delegated Act and European Council, Commission and Parliament meetings for proposed Delegated Act. Design/Methodology/Approach - The data used is historical stock price for listed company of Agriculture Sector and Plantation Sub Sector in Indonesia Stock Exchange in 23th November-7th December 2016, 10th-24th January 2018 and 4th-26th June 2018 from investing.com. The assay used in this study is statistic descriptive test, then normality test and then paired sample t-test and/or wilcoxon signed rank test. Findings - The result of this study indicates there is no difference on abnormal return in all event. That no difference happens because the event contains no information, also the investor believed more in company performance and some information is expired when stock market is open. Research implications - Research contributes to providing additional information on the impact of the revised Renewable Energy Directive on share prices in energy-producing plantation companies. Research limitations - This study has limitations, namely the trilogy meeting event intersects with the holiday and the Indonesia Stock Exchange holiday, thus creating a conflict of events whether this is the impact of the fitri holiday or because of the trilogy meeting event.